The Relationship Compliance with Fe Tablet Consumption with Anemia in Pregnant Women - Pohan, Rostina Afrida (PT Inovasi Pratama Internasional, 2022)
Oral administration of iron is one approach for the prevention and control of iron deficiency anemia. Supplementation should be given in the 2nd and 3rd trimesters, when the efficiency of absorption is increased and the risk of nausea and vomiting is reduced. The Ministry of Health in Indonesia recommends giving iron tablets to all pregnant women around 60 mg per day for 90 days. The purpose of this study was to determine the relationship between adherence to consuming Fe tablets and the incidence of anemia in pregnant women. This research uses correlation descriptive research method with cross sectional design. The population in this study were all pregnant women who visited the Sei Tualang Raso Public Health Center as many as 35 people using purposive sampling technique, data analysis was carried out with the chi-square test. The results showed that there was a relationship between adherence to consuming Fe tablets and the incidence of anemia in pregnant women at the Sei Tualang Raso Health Center, Tanjungbalai City in 2021, this was evidenced by the results of the chi-square test with p-value = 0.005. For mothers Pregnant women are expected to be more routinely check their pregnancy and obediently consume iron tablets.